"TURKIC INFLUENCE ON ENGLISH LEXICON: LOANWORDS" (International Conference on Modern Science and Scientific Studies, 2025)
This study explores the linguistic influence of Turkic languages, particularly Turkic, on the English lexicon, focusing on loanwords. These loanwords provide valuable information about the historical exchanges between Turkic-speaking peoples and English-speaking societies. The analysis examines the various categories of Turkic words that have been introduced into English, such as food, currency, titles, and everyday objects. This article examines the broader cultural influence they have had on English, as well.